"Journey of the Soul: Exploring Female Subjective Experiences Post-Umrah Pilgrimage" - Fatima, Mishal (Asian Journal of Islamic Psychology, 2024)
The manuscript investigates the significant influence of the Umrah journey on the psychological well-being of the Muslim faithful. It analyzes the range of emotions pilgrims undergo, from the anxiety of planning to the profound spiritual awakening that they experience through Mecca’s sacred rites. The research highlights the opportunities for self-improvement via the meaningful rituals of Tawaf and Sa’i, as well as the communal solidarity and connection cultivated through collective religious practices. This qualitative study delves into the subjective experiences of ten female participants, aged 25 to 35, following their completion of the Umrah pilgrimage. Utilizing snowball sampling techniques, participants were approached and interviewed face-to-face. Thematic analysis of the interview data revealed five key themes: Spiritual Renewal, Emotional Transformations, Sense of Community, Reflective Insights, and Integration into Daily Life. The findings underscore the significant impact of Umrah on participants' spiritual, emotional, and social well-being, highlighting the transformative potential of religious pilgrimages and providing valuable insights for individuals navigating their spiritual journeys.